Implementasi Penegakan Hukum Terkait Pembakaran Hutan Dan Lahan Oleh Kepolisian Di Wilayah Kabupaten Samosir - Sinaga, Opdimed Josua; Ardiyanto, Syaifullah Yophi; Hidayat, Tengku Arif (Peneliti.net, 2024)
In Indonesia, forest and land burning is a major problem. In Samosir Regency, forest and land fires occur almost every year and the area of forest and land fires is increasing. Forest and land fires are thought to originate from clearing plantation or agricultural land by burning. The police are law enforcement officers at the forefront of law enforcement related to forest and land burning. Therefore, the purpose of this thesis research is first, to find out the implementation of law enforcement related to forest and land burning by the police in the Samosir Regency area. Second, to find out the obstacles faced by the police in handling the crime of forest and land burning in Samosir Regency. Third, to find out the police's efforts in overcoming obstacles to law enforcement related to the crime of forest and land burning in the Samosir Regency area. This type of research can be classified into sociological research. With the research location located at the Samosir Regency Police, while the population and sample are all parties related to the problem under study. This research uses data sources in the form of primary data and secondary data, and data collection techniques are carried out by means of interviews. From the results of the problem research there are three main things that can be concluded. First, that law enforcement is carried out preventively (prevention) and repressively (prosecution). Second, the obstacles faced by the police in handling criminal acts of forest and land burning consist of law enforcement factors.Third, the efforts made by the police in overcoming these obstacles are, related to the lack of apparatus by requesting assistance from the North Sumatra Regional Police, then for factors related to the community, making socialization and counseling to the community. deterrent effect on the community. Third, it is advisable for the people of Samosir Regency to be able to cooperate more with the police in handling all matters relating to criminal acts of forest and land burning that occur in the Samosir Regency area